Renewable energy investments for sustainable business projects - Dinçer, Hasan; Yüksel, Serhat (Bingley, U.K. : Emerald Publishing Limited, 2023)
With such a wide range of social and economic uses, energy has become essential to global infrastructure and operations, regardless of economic or environmental cost. Renewable energy sources, where energy is obtained from natural sources such as the sun and wind, currently stand as important alternatives to fossil fuels. Yet their comparatively high installation costs continue to deter investors and further propel the planet towards catastrophic climate change. Conscious of these complexities, Renewable Energy Investments for Sustainable Business Projects identifies multiple solutions for improving the appeal of renewable energy projects. Breaking down myths about their viability and practicality, Hasan Dinçer and Serhat Yüksel take a variety of issues into consideration, including finance, competition, risk management, customer relations, technological factors and learning and growth to formulate a practical rather than theoretical examination of renewable energies and their potential. From tax advantages to hydrogen sourcing, Renewable Energy Investments for Sustainable Business Projects explores a variety of the latest practices and technological developments surrounding renewable energy, offering practical insight and tangible advice to academics and researchers in environmental management.
Chapter 1. Sustainable investments in biofuel production projects / Lyailya Maratovna Mutaliyeva and Ulf Henning Richter -- Chapter 2. The relationships between financial literacy and individual pension system and a perspective for renewable energy investments / Samet Hacilar, Ayhan Kapusuzoglu, and Nildag Basak Ceylan -- Chapter 3. Derivative financial instruments in the energy and aluminum markets / Khayrilla Abdurasulovich Kurbonov and Gabor Pinter -- Chapter 4. Environmental implications of food waste: A study on south-asian countries / Buddhadev De, Imran Hussain, and Ramesh Chandra Das -- Chapter 5. Addressing renewable energy investments with a strategic perspective / Ercan Karakeçe -- Chapter 6. A historical perspective on the benefits derived from countries' newly found energy source / Fatih Baha Aydin -- Chapter 7. Energy innovation and sustainable development: Are the nordic countries more than bumble bee? / Halim Bas and Bilal Cosan -- Chapter 8. Environmental pollution and economic sentiments: Any correlation and causal relation so far for world's highly polluting countries? / Maitree Dey, Somdip Bhukta, and Ramesh Chandra Das -- Chapter 9. The investigations for the causality connection between exports and energy consumption / Zafer Adali, Simuzar Sultan Mammadova, and Ofelya Mazanova -- Chapter 10. The nonlinear relationship between bitcoin mining and carbon emissions in the context of renewable energy / Ayyuce Memis Karatas, Emin Karatas, Ayhan Kapusuzoglu, and Nildag Basak Ceylan -- Chapter 11. Electricity production and use from renewable energy resources within the framework of Turkish legal legislation / Ergün Dilaveroglu -- Chapter 12. Overview of investments in the energy and aluminum markets / Raya Hojabaevna Karlibaeva and Anthony Nyangarika -- Chapter 13. Evaluating the advantages and disadvantages of thorium-based nuclear power plants / Serhat Yüksel, Hasan Dinçer, Çagatay Çaglayan, Alexey Mikhaylov, and Duygu Yavuz -- Chapter 14.
Includes bibliographical references and index.
Print version record.
Keywords: Clean energy investment; Renewable energy sources; Sustainable development; Business & Economics -- Environmental Economics; Environmental economics